The impact of income inequality and national wealth on child and adolescent mortality in low and middle-income countries - Joseph L. Ward; Russell M. Viner (BMC, 2017)
Abstract Background Income inequality and national wealth are strong determinants for health, but few studies have systematically investigated their influence on mortality across the early life-course, particularly outside the high-income world. Methods We performed cross-sectional regression analyses of the relationship between income inequality (national Gini coefficient) and national wealth (Gross Domestic Product (GDP) averaged over previous decade), and all-cause and grouped cause national mortality rate amongst infants, 1-4, 5-9, 10-14, 15-19 and 20-24 year olds in low and middle-income countries (LMIC) in 2012. Gini models were adjusted for GDP. Results Data were available for 103 (79%) countries. Gini was positively associated with increased all-cause and communicable disease mortality in both sexes across all age groups, after adjusting for national wealth. Gini was only positively associated with increased injury mortality amongst infants and 20-24 year olds, and increased non-communicable disease mortality amongst 20-24 year old females. The strength of these associations tended to increase during adolescence. Increasing GDP was negatively associated with all-cause, communicable and non-communicable disease mortality in males and females across all age groups. GDP was also associated with decreased injury mortality in all age groups except 15-19 year old females, and 15-24 year old males. GDP became a weaker predictor of mortality during adolescence. Conclusion Policies to reduce income inequality, rather than prioritising economic growth at all costs, may be needed to improve adolescent mortality in low and middle-income countries, a key development priority.